Urgency of Adiwiyata School for education as sustainable development - Wiwik Okta Susilawati; Yulia Darniyanti; Dian Estu Prasetyo; Lika Apreasta; Ana Novitasari (Journal of Education and Learning (EduLearn), 2020)
This research is intended to be understood; 1) the urgency of education as an environmentally sustainable development; 2) the background of implementing the adiwiyata school program at SMP Muhammadiyah 3 Yogyakarta; and 3) the implementation of the adiwiyata school program at SMP Muhammadiyah 3 Yogyakarta. The research used in this research is qualitative research. The research subjects were the chief coordinator of the adiwiyata team, and the teacher. Determination of research subjects is done by purposive sampling technique. Data collection techniques were carried out using interview, observation and documentation methods. This type of data analysis uses the Milles and Huberman model, namely reduction, data display, and drawing conclusions/verification of data. The results of this study are; 1) The concept of sustainable development is related to ethical issues, the discussion of the concept of sustainable development in the future (future) and also focuses on the problem of welfare (poverty); 2) There are a number of things underlying the implementation of the adiwiyata school program at SMP Muhammadiyah 3 Yogyakarta, both the overall background, philosophical, geographical, juridical, both organizational background; and 3) To support the growth of the values of attention problems in SMP Muhammadiyah 3 Yogyakarta can use four aspects of the Adiwiyata program, such as environmentally sound policies, implementation of environment-based policies, participatory based planning activities and management of environmentally friendly supporting facilities.